Development and Implementation of a High-Throughput High-Content Screening Assay to Identify Inhibitors of Androgen Receptor Nuclear Localization in Castration-Resistant Prostate Cancer Cells - Johnston, Paul A. (Assay Drug Dev Technol, 2016)
Patients with castration-resistant prostate cancer (CRPC) can be treated with abiraterone, a potent inhibitor of androgen synthesis, or enzalutamide, a second-generation androgen receptor (AR) antagonist, both targeting AR signaling. However, most patients relapse after several months of therapy and a majority of patients with relapsed CRPC tumors express the AR target gene prostate-specific antigen (PSA), suggesting that AR signaling is reactivated and can be targeted again to inhibit the relapsed tumors. Novel small molecules capable of inhibiting AR function may lead to urgently needed therapies for patients resistant to abiraterone, enzalutamide, and/or other previously approved antiandrogen therapies. Here, we describe a high-throughput high-content screening (HCS) campaign to identify small-molecule inhibitors of AR nuclear localization in the C4-2 CRPC cell line stably transfected with GFP-AR-GFP (2GFP-AR). The implementation of this HCS assay to screen a National Institutes of Health library of 219,055 compounds led to the discovery of 3 small molecules capable of inhibiting AR nuclear localization and function in C4-2 cells, demonstrating the feasibility of using this cell-based phenotypic assay to identify small molecules targeting the subcellular localization of AR. Furthermore, the three hit compounds provide opportunities to develop novel AR drugs with potential for therapeutic intervention in CRPC patients who have relapsed after treatment with antiandrogens, such as abiraterone and/or enzalutamide.